Criminal Misdemeanor: an Administrative Look - Starostin, Sergei A. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article focuses on the possibility and conditions for legislative fastening of the category of «criminal misdemeanor». Examines the positive and negative consequences of such a decision.